Development process resilience and sustainable development: Insights from the Drylands of Eastern Africa - Davies, J.; Robinson, Lance W.; Ericksen, Polly J. (Informa UK Limited, 2015)
Recently, the development and humanitarian relief communities have directed attention to building resilience of pastoral communities to droughts and other shocks. While resilience thinking has much to offer, using resilience as a framework for investing in disaster risk reduction and development faces numerous challenges. Development implies that people are actively changing, which poses the question of whether such changes are adaptations or transformations, or whether this is a subjective or academic distinction. The lack of clarity presents a challenge for monitoring resilience-building investments, yet such investments require indicators of impact. We argue that resilience of the system per se is not the primary goal of development and may sometimes be an impediment. We propose an alternative approach to conceptualizing resilience that more accurately reflects the concerns of the humanitarian relief and development communities, one that is based on monitoring resilience of the development process, rather than resilience of a given system.